The origins’ recovery of Potuguese and Brazilian design’s from the parallel themes between the productions’ chronological phases by Aloisio Magalhães and Raul Cunca (Revista de Ensino em Artes, Moda e Design, 2024)
This paper introduce the conceptual gaps in the history and theory of Brazilian design from a comprehensive view that searches for relationships between past and present ancestry on the Aloisio Magalhães and Raul Cunca’s productions. We observe if, after more than five hundred years of discovery of Brazil and around two hundred years after the political rupture between Brazil and Portugal, there still be be a relative approximation between the productions of the Brazilian designer Aloisio Magalhães (from 1975 to 1982) in contrast to Portuguese designer Raul Cunca (from 2012 to 2020). Although both chronologies of the prestigious designers are located in different contexts and far from the pre-independence period, would it be possible to observe similarities between the phases “Dimension of Culture” by Aloisio Magalhães and “To Inhabit the land” by Raul Cunca? Can we observe some relationships of identity and belonging between these designers? The analysis of similarities between these particular identities of these productions perhaps can show a broad orientation towards the relatively common origins of Brazilian and Portuguese design.
Keywords: design/art; history and theory of design; technique/technology; Brazil/Portugal; Aloisio Magalhães/Raul Cunca